Measurable residual disease by flow cytometry in acute myeloid leukemia is prognostic, independent of genomic profiling. (December 2022) - Ganzel, Chezi; Sun, Zhuoxin; Baslan, Timour; Zhang, Yanming; Gönen, Mithat; Abdel-Wahab, Omar I.; Racevskis, Janis; Garrett-Bakelman, Francine; Lowe, Scott W.; Fernandez, Hugo F.; Ketterling, Rhett; Luger, Selina M.; et al.
Abstract: Measurable residual disease (MRD) assessment provides a potent indicator of the efficacy of anti-leukemic therapy. It is unknown, however, whether integrating MRD with molecular profiling better identifies patients at risk of relapse. To investigate the clinical relevance of MRD in relation to a molecular-based prognostic schema, we measured MRD by flow cytometry in 189 AML patients enrolled in ECOG-ACRIN E1900 trial (NCT00049517) in morphologic complete remission (CR) (28.8 % of the original cohort) representing 44.4 % of CR patients. MRD positivity was defined as ≥ 0.1 % of leukemic bone marrow cells. Risk classification was based on standard cytogenetics, fluorescence-in-situ-hybridization, somatic gene analysis, and sparse whole genome sequencing for copy number ascertainment. At 84.6 months median follow-up of patients still alive at the time of analysis (range 47.0–120 months), multivariate analysis demonstrated that MRD status at CR (p = 0.001) and integrated molecular risk (p = 0.0004) independently predicted overall survival (OS). Among risk classes, MRD status significantly affected OS only in the favorable risk group (p = 0.002). Expression of CD25 (α-chain of the interleukin-2 receptor) by leukemic myeloblasts at diagnosis negatively affected OS independent of post-treatment MRD levels. These data suggest that integrating MRD with genetic profiling and pre-treatment CD25 expression may improve prognostication in AML. Highlights: Measurable residual disease (MRD) in AML adversely impacts outcome at all time-points during the course of treatment. Diagnostic disease-genetics, expression of CD25 and post-therapeutic MRD each independently impact prognosis.